THE PARTICULARITY OF MODAL VERBS IN FRENCH - Miyassarov Eldor Amanovich (Scholar Express Journal, 2022)
This article focuses on important aspects to consider when using modal verbs in French. The influence of modal verbs on the meaning of a sentence and the peculiarities of modal verbs are also illustrated.
Keywords: Modality; auxiliary verb; semantic forms